Subjective Well-being in China, 2005-2010: The Role of Relative Income, Gender and Location - Niaz Asadullah; Saizi Xiao; Emile Kok-Kheng Yeoh (Institute for the Study of Labor (IZA), 2016)
We use data from two rounds of the Chinese General Social Survey (CGSS) to study the determinants of subjective well-being in China over the period 2005-2010 during which self-reported happiness scores show an increase across all income groups. Ordered probit regression analysis of well-being reveals large influence of gender, rural residency and household income. After controlling for demographic attributes, health, unemployment status, household size, agricultural hukou (household registration identity) and education status, household assets, the influence of past and future income and province dummies, we find that women, urban residents and people with higher income are happier in China. More schooling, better health and being employed are positively and significantly correlated with well-being. Sub-sample s reveals that the rich only care about relative income whereas the effect of absolute income dominates in case of the poorer section. The influence of absolute income is larger among women compared to men and in turn explains why women, despite being poorer, are happier in China, conditional on socio-economic differences. On the other hand, rural residents are poorer than urban residents so that conditional on having the same income, there is no rural-urban happiness gap. Our results suggest that while further decline in poverty will enhance well-being in China, policies that reduce rural-urban and gender inequalities are also likely to boost well-being.
Keywords: O12; I30; I31; 330; gender; happiness; inequality; poverty; unemployment; well-being